E-CATALOGUE SEBAGAI BASIS DATA DAN MEDIA PROMOSI BUKU KARYA MAHASISWA PRODI PENERBITAN - Akmalia, Nurul; Suratni, Suratni; Yuliana, Refi; Cempaka, Putri Surya; Yakob, Freddy (Jurnal Ilmiah Publipreneur, 2023)
Publishing is one of the creative industry sub-sectors that continues to grow in Indonesia. This research was carried out as a form of implementing digital publishing knowledge and digital marketing communication knowledge in the Publishing Study Program at Polimedia. The purpose of this research is to explain the creation of a digital catalogue that functions as an archive or database of the works of Publishing Study Program students, and as a promotional medium to a wider audience, as well as a capital for future entrepreneurial practices. The method used is qualitative-descriptive research with data collection techniques through literature/document studies, observation, and interviews. In practice, the research team carried out four stages of work, namely: (1) planning the concept of a website and digital catalogue, (2) compiling data and creating a manual catalogue, (3) compiling website content and website design, and (4) data integration (catalogue) to the website. The results obtained from this applied research are the establishment of a website http://katalog-bukupolimedia.my.id as a digital catalog of works by the Publishing Study Program students at Polimedia.